SOCIO-DEMOGRAPHIC PROFILE OF HEPATITIS B AND C INFECTIONS IN THE MUNICIPALITY OF ANÁPOLIS, GOIÁS (CIPEEX, 2025)
Viral hepatitis B and C are the subtypes of greatest epidemiological relevance in Brazil, with high morbidity and mortality rates due to their clinical characteristics and complications. The aim of this study is to describe the epidemiological data of the municipality of Anápolis, Goiás, regarding hepatitis B and C infection. This is a descriptive, quantitative, observational, and cross-sectional study, using data provided by the Municipal Health Department of Anápolis from the Viral Hepatitis Notification Unit in the municipality. Data from notification forms were analyzed regarding the sex and age group of hepatitis B and C cases in the municipality from 2019 to 2024. For hepatitis B, 433 cases were reported during the study period, with a predominance among males (n=247) and in the 35–49 age group (n=157). As for hepatitis C, a total of 144 cases were reported, 85 of which were male, and the age group with the highest incidence was 50-64 years (n=50). It is concluded that in the municipality of Anápolis there is a higher incidence of hepatitis B compared to hepatitis C, and that for both types, cases are predominantly among males and adults.
Keywords: Hepatitis B; Hepatitis C; Epidemiology